(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The article deals with the ideological and stylistic features of the work of the talented Kyrgyz poet Alykul Osmonov. The author notes the features inherent in the poet’s lyrics: kindness, optimism, love for the Motherland, , service to the high, great love for the nature of the native land.